Association of Maternal Hypothyroidism With Cardiovascular Diseases in the Offspring - Miao, Maohua; Liu, Hui; Yuan, Wei; Madsen, Nicolas; Yu, Yongfu; László, Krisztina D.; Liang, Hong; Ji, Honglei; Li, Jiong (Frontiers in Endocrinology, 2021)
Background: No previous study has examined the effect of maternal hypothyroidism on a broad spectrum of cardiovascular disease (CVD) endpoints in the offspring. Methods: A nationwide population-based cohort study based on the linkage of several Danish nationwide registries was conducted to explore whether maternal hypothyroidism is associated with offspring’s CVD. Altogether 1,041,448 singletons born between the 1st of January 1978 and the 31st of December 1998 were investigated from the age of 8 years to the 31st of December 2016. Exposure was maternal diagnosis of hypothyroidism across lifespan and the outcome of interest was a CVD diagnosis in the offspring. Cox regression models were performed to estimate the hazard ratios (HRs) of CVD. Results: Offspring born to mothers with hypothyroidism had an increased risk of CVD (hazard ratios (HR)=1.23, 95% confidence interval (CI): 1.12-1.35), and of several subcategories of CVD including hypertension, arrhythmia, and acute myocardial infarction in offspring. The magnitude of association was the most pronounced in an exposure occurring during pregnancy (HR=1.71, 95% CI: 1.10-2.67), which is consistent across all the subgroup analysis, including sibling analysis. Conclusions: Maternal hypothyroidism is associated with an increased risk of CVD in offspring. Thyroid hormone insufficiency during pregnancy may predominantly contribute to the observed associations; however, the effects of a shared genetic background and a time-stable familial environment/lifestyle factors cannot be excluded.